1997
DOI: 10.1021/ma9614306
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Investigation on Metal Free Anionic Polymerization of Methyl Methacrylate Using Tetraphenylphosphonium as the Counterion in Tetrahydrofuran

Abstract: The anionic polymerization of methyl methacrylate using tetraphenylphosphonium triphenylmethanide as an initiator proceeds in a living manner even at room temperature. The rate constants of propagation were measured between −20 and +20 °C using a flow tube reactor. At 0 °C the reaction half-lives range from 0.3 to 1 s. The polymerization follows first-order kinetics with respect to monomer conversion (with a short induction period) and shows a linear dependence of the number-average degree of polymerization on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
5
44
0
Order By: Relevance
“…5 shows the Arrhenius plot of the propagation rate constants, k p , compared to other counterions. The rate constants in presence of the P 5 + cation are much higher than those obtained with metal cations 1) and even higher than for the tetraphenylphosphonium ion where dormant ylides have been shown to be the majority of species 36) . Ylide formation is not possible for the P 5 + cation.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…5 shows the Arrhenius plot of the propagation rate constants, k p , compared to other counterions. The rate constants in presence of the P 5 + cation are much higher than those obtained with metal cations 1) and even higher than for the tetraphenylphosphonium ion where dormant ylides have been shown to be the majority of species 36) . Ylide formation is not possible for the P 5 + cation.…”
Section: Resultsmentioning
confidence: 67%
“…Zagala and Hogen-Esch 35) successfully used the tetraphenylphosphonium (TPP + ) counterion in the polymerization of MMA and obtained polymers with narrow molecular weight distribution at ambient temperature. Our kinetic studies 36) supplemented by NMR evidence 37) revealed that TPP + ion pairs are in a dynamic equlibrium with dormant ylides.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…All experiments were carried out in a specially designed flow-tube reactor with a mixing time of a 1 ms and reaction times of 2 ms f s s 20 s. [15,[33][34][35] The effective temperature, T eff , of the each experiment was determined using Eq. (1) [36] T eff = T m + 0.55 DT…”
Section: Kineticsmentioning
confidence: 99%